Metamorphism and its bearing on geosystems - Palin, RM (Elsevier, 2021)
The Earth is a dynamic, ever-changing planet, and there exist many feedbacks and cycles that operate within and between its subsystems. Interactions between processes operating in the solid Earth, atmosphere, hydrosphere, and biosphere have become increasingly better understood in recent years, given advances made in observational techniques that provide data at ever-higher spatial and temporal resolution. Indeed, the relationships that metamorphism has with classically disparate areas of Earth science, such as biogeoscience, economic geology, and natural hazards, are becoming progressively clearer as more petrologists are applying their knowledge, tools, and techniques to cross-disciplinary studies. In this review, I outline the role that metamorphism and metamorphic rocks play within various geosystems and indicate some areas in which directed future research may lead to notable breakthroughs in our understanding of the structure and functioning of the Earth as a whole.